The Development Strategy of Intellectual Property Rights and the Quest for Materials Copyrighted in Islamic Higher Education (UINSI Samarinda, 2019)
Intellectual Property Rights becomes a serious discussion in some universities, especially in the Perguruan Tinggi Keagamaan Islam Negeri (PTKIN, State Islamic Higher Education system). The lack of copyrighted academic works in some PTKIN is the background why this article is published. This article aims at looking some development strategies that are exist in several universities in Indonesia. Using empirical studies, this article explores some experiences of three universities related to the strategy of developing intellectual property rights. These three universities are Universitas Islam Indonesia Yogyakarta (UII, Islamic University of Indonesia), Universitas Islam Negeri Sunan Gunung Djati Bandung (UIN Bandung, Sunan Gunung Djati State Islamic University of Bandung) and Institut Agama Islam Negeri Surakarta (Surakarta State Institute of Islamic Studies). This article finds that the development of intellectual property rights institutions in higher education includes four important things: mission, goals, strategies and policies. The conclusion of this article confirms that several universities have established institutions for strengthening intellectual property rights by having clear visions and measurable targets, so as to produce the right policies. Meanwhile, some higher education institutions have not established yet institution of Intellectual Property Right. However, several universities have been starting to strengthen the protection of intellectual property rights by raising some lecturers’ research to be copyrighted academic works.Keywords: Intellectual property rights, strategies for the development of IPR, Universities and IPR in Indonesia.